Considerations for implementating market based mechanisms in combating climate change in South Africa - Marais, Frans (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2026)
Since the first period of the Kyoto Protocol, there has been a growing concern that the burden of reducing greenhouse gas emissions should not only be borne by developed countries, but developing countries as well. South Africa, as the 18th highest emitter of greenhouse gases in the world and highest in Africa, has a significant responsibility to reduce its emissions levels. The South African government is currently in the process of implementing a carbon tax for its short term response to climate change and considering the implementation of a carbon market as a medium to long term response to climate change. Both of these market based mechanisms are widely deemed effective in the mitigation of greenhouse gas emissions by economists, however are also known to have negative social and economic implications upon an economy. This study identifies these implications and attempts to provide considerations on how to alleviate the implications through the most appropriate process of revenue recycling. The negative effects of Implementing a carbon tax or carbon market could be severe as and not limited to: a significant decline in GDP, a reduction in the standard of living for certain households, a fall in a country's exports and even an increase in poverty. South Africa's environmental and development policies place a strict precedence on the protection of the poor and the prevention of economic hardship induced by such policies. This places significant importance on the prevention of these externalities from occurring. A primary means of doing so is through the process of revenue recycling, however, certain channels of revenue recycling are by no means helpful, hence the most appropriate channel needs to be identified. The study carried out a multiple case study analysis on Ireland, Mexico, New Zealand and Norway, to determine what effects a carbon tax had on their economies and how these effects were mitigated through carbon tax revenue recycling. An additional analysis of the EU ETS was carried out to determine how the EU ETS was implemented and the controversies and concerns that arose during its implementation. The findings of this analysis were then compared to a number of South African economist's case studies, and the most appropriate method of revenue recycling identified and possible solutions to the EU ETS controversies found. The study concludes that a food subsidy has the potential to provide positive effects on welfare employment and GDP
Keywords: Climatic changes -- Economic aspects -- South Africa